Relationship-Based Care and Behaviours of Residents in Long-Term Care Facilities. (12th January 2014) - Desrosiers, Johanne; Viau-Guay, Anabelle; Bellemare, Marie; Trudel, Louis; Feillou, Isabelle; Guyon, Anne-Céline
Abstract : Introduction . In long-term care (LTC), person-centred approaches are encouraged. One such approach, relationship-based care (RBC), aims among other things to reduce residents' agitated behaviours. RBC has been used in numerous Quebec LTC facilities over the past decade but it has never been studied. Objective . Explore correlations between use of RBC by trained caregivers and the frequency of agitated and positive behaviours of residents with cognitive impairments. Methods . Two independent raters observed fourteen caregiver/resident dyads in two LTC facilities during assistance with hygiene and dressing. Checklists were used to quantify caregivers' RBC use and residents' agitated and positive behaviours. Results . Scores for RBC use were high, suggesting good application of the approach by caregivers. Correlation analyses showed that offering residents realistic choices and talking to them during care were associated with both positive and agitated behaviours (P from 0.03 to 0.003). However, many other components of RBC were not associated with residents' behaviours during care. Conclusions . There were only a few quantitative links between the RBC checklist items and the frequency of agitated or positive behaviours. Other studies with a more rigorous research design are needed to better understand the impact of relationship-based care on residents' behaviours.